Binding of Zn2+ to rat liver fructose-1,6-bisphosphatase and its effect on the catalytic properties. - Pedrosa, F O (1977)
Rat liver fructose-1,6-bisphosphatase (D-fructose-1,6-bisphosphate 1-phosphohydrolase, EC 3.1.3.11) contains 12 binding sites for Zn2+ per molecule, or 3 per subunit, as determined by gel filtration and by precipitation of an insoluble Zn2+-enzyme complex. The first set of sites binds Zn2+ with very high affinity, and the binding constant for these sites could not be determined. The average values of the dissociation constants for the second and third sets of sites were approximately 0.4 and 1.5 muM, respectively. The third set of sites, having lowest affinity, appears to be identical to the binding sites for the activating cation, Mg2+, and the binding of Zn2+ to this set of sites is prevented by the addition of Mg2+. Binding of the first 4 equivalents of Zn2+ yields an enzyme of intermediate activity, while the binding of 8 equivalent results in almost complete inhibition of catalytic activity. Thus Zn2+ appears to function as both an activator and a negative allosteric regulator of fructose-1,6-bisphosphatase activity.